The Urgency of General Principles of Good Governance in the Continuity of Population Administration Activities - Effi Awiska Putri Widoyo (UM Purwokerto Press, 2023)
Population administration activities cannot be separated from government intervention. This is in line with one of the main government functions, which is to provide public services as a form of general government duties to realize public welfare. The performance of the central and local governments must be in accordance with the General Principles of Good Governance to be in line with the interests of the community. To optimize Population Administration Services for Making Electronic Identity Cards (KTP el) requires an understanding of the principles contained in the General Principles of Good Government. The general principles of good governance can be understood as general principles that are used as the basis and procedures for proper government administration. In addition, it is also necessary to consider the factors inhibiting the making of Electronic Identity Cards (KTP el) in order to obtain appropriate improvement efforts. The method used is a qualitative approach with reference to Good Government Theory. The results of the study can be concluded that the population administration service of KTP el has been running, but it is not in accordance with the application of good service principles and there are still several obstacles faced.